QUALITY ASSURANCE ORGANISATIONAL AND MANAGEMENT STRUCTURE IN THE EUROPEAN UNION - Mospan, Natalia (Educological discourse, 2018)
The article presents the features of the quality assurance management system of higher education in the EU. Besides, the analysis of the quality assurance system in Europe, namely its external and internal organs is in th the center of attention. External mechanisms include education quality assurance regulators at the EU and the EHEA level and national regulators of education quality assurance at the level of Member States. Internal mechanisms are made up of quality control departments within HEIs. It was concluded that the organizational and administrative structure adjustment of standards and quality assurance of education in the EU subject to their own hierarchy, where each mechanisms interact to ensure the quality of the various higher education systems. This system of organizational and management structures regulation of standards and quality assurance of education in the EU allows to implement universe standards of quality assurance in higher education in all EU Member States and countries in the EHEA. However, despite the establishment of relatively universe shape of quality assurance system, there are significant differences in approaches to the system at the national level.